PENERAPAN KONSEP HIJAB PADA RUMAH TINGGAL PERKOTAAN - Ronim Azizah (Jurnal Teknik Sipil dan Perencanaan)
This research identified the housing design which implement the hijab concept with limited square land. According to this limitation, the housing design will be minimalist. In general, a house consist of rooms for settlement function such as living room, bedroom, bathroom and kitchen. This general room arrangement leads to an unclear division of public and private zone. Therefore, architecture functions as a tool to accommodate human activity and hijab in housing design to implement Islam ideology that manage human live-hood. Through this fusion of architecture and hijab arrangement, the Islamic housing design can be created. this research is using descriptive method which identified the extend of hijab concept implementation in urban housing design with limited square lot. Data analysis use several parameters (1) Physical hijab such as room arrangement, wall, door and window and (2) non physical hijab such as the user's activity or behavior. the result shows that hijab concept in urban housing design consist of (1) physical hijab such as room arrangement that divide public and private zone and (2) non physical hijab such as behavior or etiquette of visiting which implementing Islamic culture.